2012
DOI: 10.1039/c2dt31075a
|View full text |Cite
|
Sign up to set email alerts
|

Transfer hydrogenation with a ferrocene diamide ruthenium complex

Abstract: The use of a 1,1'-ferrocenediamide ruthenium complex as a mediator for base-free transfer hydrogenation is reported. Ketones were transformed to their respective alcohols at room temperature in 36-99% conversions with turnover frequencies up to 339 h(-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Currently, we are exploiting the rich chemistry enabled by flexible and redox-noninnocent ferrocene-based ligands for rare-earth metals, actinides, and other metals including late transition metals in order to study further unusual transformations and applications to material synthesis. 42,48,53,87…”
Section: ■ Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, we are exploiting the rich chemistry enabled by flexible and redox-noninnocent ferrocene-based ligands for rare-earth metals, actinides, and other metals including late transition metals in order to study further unusual transformations and applications to material synthesis. 42,48,53,87…”
Section: ■ Summarymentioning
confidence: 99%
“…Our group has taken a different approach in order to achieve the goal of coordination flexibility and redox activity (Chart g,h). , Instead of using a purely organic ligand, we reasoned that an organometallic ligand should serve as an excellent candidate. Such a ligand needs to fulfill the following requirements: (1) the organometallic part should be chemically inert under common reaction conditions; (2) the metal should be redox-active; (3) the organometallic fragment should be able to act as a weak donor.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has been interested in understanding the synergistic effects resulting from the interaction of ferrocenebased ligands with metals that exist in various oxidation states. [6][7][8][9][10][11][12][13][14] We have shown that such ligands are capable of influencing bonding and enhancing reactivity of transition metals, [8][9][10][11] lanthanides, [14][15][16] as well as actinides. [17][18][19] For uranium, we have observed a wide range of reactivity between tetravalent uranium complexes supported by such ligands and heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of imine 10 is quantitative and the secondary amine 11 was characterized in the 1 H NMR by its H –N at 1.23 ppm and in the 15 N NMR by a signal at −332.0 ppm. Such secondary amines are valuable compounds since, notably, amido complexes are in principle accessible by simple deprotonation …”
Section: Resultsmentioning
confidence: 99%